Enhancement Mechanism of Fish-Scale Surface Texture on Flow Switching and Mixing Efficiency in Microfluidic Chips - Zheng, Lu (Langmuir : the ACS journal of surfaces and colloids, 2023)
Surface textures have a significant influence on surface-functional properties, which provide an alternative solution to create an accurate control of microfluidics flow. This paper studies the modulation ability of fish-scale surface textures on microfluidics flowing behavior on the ground of the early research on vibration machining-induced surface wettability variation. A microfluidic directional flow function is proposed by modifying the wall of the microchannel at the T-junction with different surface textures. The retention force caused by the surface tension difference between the two outlets in the T-junction is studied. In order to investigate the influence of fish-scale textures on the performance of the directional flowing valve and micromixer, T-shaped and Y-shaped microfluidic chips were fabricated. The experimental results indicated that with the aid of the fish-scale surface textures generated by vibration-assisted micromilling, directional liquid flow can be achieved at a specific input pressure range and the mixing efficiency of microfluidics can be improved dramatically